Atopic march in pediatrics: genotype-associated mechanisms Part 2. Perspective genotype-associated mechanisms and markers of atopic disorders in children - V.O. Dytiatkovsky (Zaslavsky O.Yu., 2017)
The review deals with the data of studies covering last 10 years held in populations of different countries concerning the association of atopic diseases, which compose the atopic march in children (atopic eczema, allergic rhinitis, allergic rhinoconjunctivitis, bronchial asthma) with genes pathologic mutations (single nucleotid polymorphisms - SNP), which encode the molecules participating in allergic inflammation in the skin and mucosae. The review has been made using the PubMed as a search tool. There is analysis of studies provided on the candidate gens for allergic inflammation - interleukin-1-like-receptor-1, sphyngolipid synthesis regulator, glucorticoid receptor gene, programmed cell death gene 4. There are also provided the candidate markers for the severity of atopic diseases course, particularly, atopic eczema: vitamin D, thymus and activation regulated chemokine, TARC/CCl17 and cutaneous T-cell attracting chemokine, CTAC/CCL27. There has been proposed conducting the studies of provided SNP and allergic inflammation markers on Ukrainian pediatric population for working out the personalized genotype-associated approach for diagnosing and management of atopic diseases in Ukrainian pediatric population.